Correlation of microalbuminuria with neuropathy in type-II diabetes mellitus patients - Bariha, P. K.; Tudu, K. M.; Kujur, Shiny Thomas (International Journal of Advances in Medicine, 2018)
Background: The microvascular and macrovascular complications in diabetes mellitus resulting in microalbuminuria and diabetic neuropathy in common in developing country like India. The aim of the study has been undertaken to emphasis upon the association of microalbuminuria with neuropathy. Methods: The study was undertaken among 124 Type-II diabetes patients in the Department of Medicine, VIMSAR, Burla, Odisha between October 2015 to September 2017. Detail history, clinical examination, BMI, laboratory investigation like FBS, PPBS, HbA1C, nerve conduction study was done, and data were analysed and compiled. Results: Out of 124 patients the mean age of male patients in the study was 49.75 years and that of female patients was 50.36 years. The mean age of the study population was 50.18 years. The mean BMI in patients with and without microalbuminuria was 23.95±2.04kg/m2 and 21.57±2.89kg/m2 respectively. The mean HbA1C value in patients with and without microalbuminuria was 9.96±3.380 and 8.75±3.25 respectively. Conclusions: Microalbuminuria is significantly associated with presence of neuropathy. The most common type of neuropathy observed in this study was distal symmetrical sensory motor neuropathy. Hence, microalbuminuria has an important role as a biochemical marker for risk factor evaluation of microvascular complications in type 2 diabetes mellitus.